Identification And Phytochemical Testing Of Traditional Medicinal Plants Of The North Buton Community - -, Ridwan (Jurnal Sains dan Pendidikan Biologi, 2023)
Medicinal plants play a very vital role in their use for medicine, in addition to providing ecological, economic and cultural benefits. Since ancient times, plants have been used as a source of effective and safe medicines. Plants can have medicinal properties because they contain secondary metabolites or other bioactive compounds. This study uses samples of medicinal plants that have been used by the people of North Buton as traditional medicine for hundreds of years. This plant has never been reported in previous studies. This study aims to determine the types of medicinal plants and the phytochemical content contained in these plants. The research was conducted with several stages of identification and phytochemical testing. The phytochemicals analyzed included flavonoid alkaloids, tannins, steroids, terpenoids, saponins and phenols. Phytochemical tests were carried out on plant organs, namely roots, stems and leaves. The results of plant identification showed that the plant was a genus of Embelia. Furthermore, the results of phytochemical tests showed that the roots and stems of Embelia sp. contains flavonoids, alkaloids, steroids, saponins, tannins and phenols. Furthermore, the leaves of Embelia sp. contains alkaloids, steroids, saponins, tannins and phenols.